Two phase olive mill waste valorization. Hydrochar production and phenols extraction by hydrothermal carbonization - Gimenez, Marianela (2020)
Olive oil is one of the main products from the Central-Western Region of Argentine Republic, which is mostly obtained by continuous two-phase centrifugation systems. Two-phase-olive-mill-waste (TPOMW) or Alperujo is the main waste generated by this process. This research was conducted in order to give value to this waste by producing hydrochar and phenolic antioxidant compounds, products of great interest today. For this, the hydrothermal carbonization process was applied, an effective technique to synthesize a broad range of carbon-rich materials. In this study the extraction of typical phenolic compounds of the olive from the liquid phase generated in this process was also analyzed. Box Benhken response surface method was applied to obtain the optimal values of the operating conditions of the process and the selected response variables: higher heating value of the hydrochar (HHV) and content of total phenol concentration (TPC) in the liquors. Values of 31.70 MJ.kg-1 and 4429 mL.g-1 were obtained, respectively. Effectiveness of hydrothermal carbonization for hydrochar was evidenced, achieving 70% increases in the value of HHV and 40% of carbon concentration, compared to raw alperujo. In addition, values of 1.36 and 0.17 were obtained for the H/C and O/C ratios, respectively, and energy yield of 85%. Furthermore, the physico chemical properties evaluated by scanning electron microscopy and Fourier transform infrared spectroscopy, showed their potential application as adsorbent precursor. In the liquid fraction obtained, phenols could be extracted in attractive concentrations, increasing the content of hydroxytyrosol and tyrosol 3 and 9 times with respect to the untreated alperujo, respectively.